Multiple solutions of Choquard equations in ℝ2 with critical exponential growth via penalization method. (3rd February 2021) - Zhang, Hui; Xu, Junxiang
Abstract : We deal with the singularly perturbed Choquard equation in the plane with critical exponential growth in the sense of the Trudinger–Moser inequality. Under a local condition imposed on the potential, we show the multiplicity and concentration of positive solutions via penalization technique and variational methods.